If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(n + -6) + 7n = 8 Reorder the terms: 7(-6 + n) + 7n = 8 (-6 * 7 + n * 7) + 7n = 8 (-42 + 7n) + 7n = 8 Combine like terms: 7n + 7n = 14n -42 + 14n = 8 Solving -42 + 14n = 8 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 42 + 14n = 8 + 42 Combine like terms: -42 + 42 = 0 0 + 14n = 8 + 42 14n = 8 + 42 Combine like terms: 8 + 42 = 50 14n = 50 Divide each side by '14'. n = 3.571428571 Simplifying n = 3.571428571
| x=3(2y+1) | | 4x+50=-14 | | 5asdrf=7asdrf | | 3t-t-8=t-5 | | 9x+1=27x | | 8+x-5x=8+44 | | 4x^2-30x+1=0 | | 5x-14+10=180 | | (5-9a^3)+(4a^2+6a-3)= | | x+5x=x | | X-7x+9=-47 | | Y=(3+4k)x | | 2x+45-9x=10 | | (6x^3-4x^2+x-9)-(3x^2+7x+3)= | | 5a+2=2a-6 | | X-0.65x=273 | | 15x+20x=70 | | x+3y-21=0 | | X-1/2x=10 | | 50/6.25= | | (5x^2-2x-1)-(3x^2+7x+3)= | | 3n+6=10-n | | a+4b=-4 | | -4+4x=3x+2 | | -4.7=g/-3.2 | | -3x+4=-4x+1 | | X^2-6y+8=0 | | 2x-7=13-3x | | -10(x-5)+76=-12-12 | | 3/2n-7/2n=7/2 | | y=0*ln(0) | | 3+x=X+2 |